Quatre-Vingt-Neuf Revisited: Social Interests and Political Conflict in the French Revolution - Comninel, George (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1989)
AbstractFifty years after its publication, Quatre-Vingt-Neuf — Georges Lefebvre's classic statement of the social interpretation of the French Revolution — is widely thought to have been discredited. Revisionist historians have effectively challenged the idea that the bourgeoisie was a revolutionary capitalist class overthrowing feudalism, and this has been taken to repudiate both Lefebvre's interpretation and Marxist history generally.Yet the new revisionist orthodoxy has been unable to provide a credible alternative account of the origins and course of the Revolution. A “new” social interpretation is therefore suggested which, ironically, is very close to that originally offered by Lefebvre for, while the idea of a bourgeois-capitalist class revolution clearly is refuted by the historical evidence, a return to Quatre-Vingt-Neuf reveals that this concept did not play a central role in Lefebvre's account. Nor is it integral to Marx's historical materialist method of analysis. Indeed, a fresh historical materialist class analysis of the ancien régime supports a very different social interpretation than that of “bourgeois revolution,” one largely consistent with Lefebvre's interpretation of the complex but integral social revolution unleashed in 1789.